Imagining rhetoric : composing women of the early United States - Eldred, Janet Carey; Mortensen, Peter, 1961- (Pittsburgh : University of Pittsburgh Press, 2002)
"Imagining Rhetoric examines how women's writing developed in the decades between the American Revolution and the Civil War, and how women imagined using their educations to further the civic aims of an idealistic new nation."
"Using a variety of sources, including novels, textbooks, letters, diaries, and memories, Janet Carey Eldred and Peter Mortensen examine the provenance, authority, and evolution of what they term "liberatory" civic rhetoric - from the early days of the republic through the antebellum years - especially as it shaped women's rhetoric and education. Imagining Rhetoric recovers what women in the early U.S. imagined instruction and practice in composition should be, and shows how this imagination shaped the possibilities and limitations of female civic rhetoric."--Jacket
Introduction: The Tradition of Female Civic Rhetoric -- Schooling Fictions -- A Commonplace Rhetoric: Judith Sargent Murray's Margaretta Narrative -- Sketching Rhetorical Change: Mrs. A.J. Graves on Girlhood and Womanhood -- The Commonsense Romanticism of Louisa Caroline Tuthill -- Independent Studies: Almira Hart Lincoln Phelps and the Composition of Democratic Teachers -- Conclusion: Rhetorical Limits in the Schooling and Teaching Journals of Charlotte Forten -- From Hannah Webster Foster's The Boarding School (1798) -- From Judith Sargent Murray's The Gleaner (1798) -- From Louisa Caroline Tuthill's The Young Lady's Home (1839) -- From Almira Hart Lincoln Phelps's Lectures to Young Ladies (1833).
Includes bibliographical references (pages 261-273) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Forten, Charlotte L; Journal (Forten, Charlotte L.); English language -- Rhetoric -- Study and teaching -- United States -- History; English language -- Rhetoric -- Study and teaching -- Sex differences; American prose literature -- Women authors -- History and criticism; Women -- Education -- United States -- History -- 19th century; Women and literature -- United States -- History -- 19th century; Women teachers -- United States; Rhetoric -- Sex differences; Femmes -- Éducation -- États-Unis -- Histoire -- 19e siècle.; Femmes et littérature -- États-Unis -- Histoire -- 19e siècle.; Enseignantes -- États-Unis.; Rhétorique -- Différences entre sexes; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; American prose literature -- Women authors; English language -- Rhetoric -- Study and teaching; English language -- Rhetoric -- Study and teaching -- Sex differences; Women and literature; Women -- Education; Women teachers; United States; Rhetorik; Frau; Prosa; USA; Geschichte 1790-1850.; Englisch; 1800-1899; Criticism, interpretation, etc; History